A COMPREHENSIVE REVIEW OF WOODFORDIA FLORIBUNDA SALISB. - Sangeeta, *Kumari; D.C, Singh; Suresh, Chaubey; Chhavi, Yadav (International Journal of Ayurveda and Pharma Research, 2016)
Indian medicinal plants are the essence of Ayurveda and Ayurvedic treatments. When used judicially and clocking with the basic principles they produce miraculous effects. Fire flamed Bush (Woodfordia floribunda salisb), commonly called as Dhavari, Dhataki, belongs to the family Lythraceae. It is an important medicinal plant of tropical and subtropical India. Dhataki is a deciduous shrub, usually with a much fluted stem, spreading branches, 1-3 m high, rarely up to 7 m, commonly occurring throughout North India, ascending to an altitude of 1,500 m in the Himalayas, but rather scarce in South India. Acharya Charak quoted it among the fermenting agents (Asava yoni) and described under Purisasangrahniya, Mutravirajaniya and Sandhaniya group of drugs. The reported pharmacological activities of Woodfordia floribunda salisb. are antitumor activity, DNA inhibitory activity, immunomodulatory activity, antioxidant activities, antihyperglycemic activity, anti- inflammatory and analgesic properties, antimicrobial activity, hepatoprotective activity, etc. Dhataki is one of the major ingredient of many important formulations used in Ayurvedic system of medicine such as Dhatakyadi taila, Dhatakyadi curna, Pusyanuga curna, Brhat Gangadhara curna, Arvindasava. So this review paper is an attempt of the author to provide details of this medicinal plant Dhataki about its classical references, synonyms, botanical description, phytochemical and pharmacological activity and classical medicinal uses.